THE INFLUENCE OF PRICES, SALES PROMOTIONS DURING LIVE STREAMING AND THE ATTRACTIVENESS OF ADVERTISEMENTS ON IMPULSIVE BUYING DECISIONS IN THE SHOPEE MARKETPLACE - Kurniasari, Rizki Sefya; Setianingsih, Wahyu Eko; Tyas, Wenny Murtalining (Dynamic Management Journal, 2024)
The development of information technology and the online world continues to progress very rapidly. Especially entering the modern era, there are very many people who use the internet as a marketing and business media so that there are many marketplaces that have developed in Indonesia, one of which is the Shopee marketplace. The number of marketplaces makes competition tighter, therefore every marketplace is required to do the best strategy to attract consumer interest. This study aims to determine the effect of price, sales promotion, and advertising appeal on impulse buying decisions at the Shopee marketplace. This research includes a quantitative approach using numerical or numerical data. The sample in this study were 150 people who live in the Jember City area who live in Sumbersari District and are Shopee members. The sampling technique used in this study is nonprobability sampling with purposive sampling method. The sampling technique used a questionnaire distributed via google form. Hypothesis testing in this study using a partial test (t test). The results showed that Price (X1), Sales Promotion (X2), and Advertising attractiveness (X3) partially had a significant effect on impulse purchases (Y).